Finding a Middle Ground: Exploring the Impact of Patient- and Family-Centered Design on Nurse–Family Interactions in the Neuro ICU. (October 2015) - Rippin, Allyn S.; Zimring, Craig; Samuels, Owen; Denham, Megan E.
Objective: This comparative study of two adult neuro critical care units examined the impact of patient- and family-centered design on nurse–family interactions in a unit designed to increase family involvement. Background: A growing evidence base suggests that the built environment can facilitate the delivery of patient- and family-centered care (PFCC). However, few studies examine how the PFCC model impacts the delivery of care, specifically the role of design in nurse–family interactions in the adult intensive care unit (ICU) from the perspective of the bedside nurse. Methods: Two neuro ICUs with the same patient population and staff, but with different layouts, were compared. Structured observations were conducted to assess changes in the frequency, location, and content of interactions between the two units. Discussions with staff provided additional insights into nurse attitudes, perceptions, and experiences caring for families. Results: Nurses reported challenges balancing the needs of many stakeholders in a complex clinical environment, regardless of unit layout. However, differences in communication patterns between the clinician- and family-centered units were observed. More interactions were observed in nurse workstations in the PFCC unit, with most initiated by family. While the new unit was seen as more conducive to the delivery of PFCC, some nurses reported a loss of workspace control. Conclusions: Patient- and family-centered design created new spatial and temporal opportunities for nurse–family interactions in the adult ICU, thus supporting PFCC goals. However, greater exposure to unplanned family encounters may increase nurse stress without adequate spatial and organizational support.